RAISING AWARENESS OF LEARNING STRATEGY IN LISTENING FOR TERTIARY EFL LEARNERS - SUYONO SUYONO (Ta'dib, 2010)
Suffering from lacks of supporting instructional materials and teaching methodology are suspected to be the sources of students’ low ability in listening. Other source that influences the students’ insufficiency is lack of learning strategy. In line with the awareness of learning strategy in listening, such concept is believed to contribute promising solution for two main reasons: clear theoretical framework and empirical experiences taking place around the world. Consequently, it is considerably important to teach listening by applying the concept of learning strategy within classroom learning process and outside as well.Key words:   learning strategy, listening, listening strategies, strategy-based instruction